2012
DOI: 10.1143/jjap.51.113101
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of YBa2Cu3O7-δ Patterned Film Using Metal Organic Deposition with Electron Beam Irradiation

Abstract: A microfabrication method to produce YBa2Cu3O7-δ (YBCO) was investigated using the metal organic deposition (MOD) process with electron beam (EB) irradiation. EB irradiation causes decomposition of the C–H and –COO– bonds and desorption of oxygen atoms in the metal octylate precursors. Therefore, oxidation of metal atoms could become harder for the MOD with EB irradiation than for the conventional MOD because of lack of oxygen, and consequently a longer prefiring time is required to ensure oxidation of the met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…For the future progress of the industry, nonvacuum processes must be adopted to decrease manufacturing cost. In this present study, MgO thin films were formed by metalorganic decomposition (MOD), [8][9][10] a liquid-phase growth method. Moreover, high-quality ultrathin films of Co nanoparticles were formed in an island pattern on a substrate in a short time in vacuum to form seed crystals and promote the growth of MgO crystals.…”
Section: Introductionmentioning
confidence: 99%
“…For the future progress of the industry, nonvacuum processes must be adopted to decrease manufacturing cost. In this present study, MgO thin films were formed by metalorganic decomposition (MOD), [8][9][10] a liquid-phase growth method. Moreover, high-quality ultrathin films of Co nanoparticles were formed in an island pattern on a substrate in a short time in vacuum to form seed crystals and promote the growth of MgO crystals.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been reported that some precursor materials for MOD have electron-beam (EB) sensitivity. [1][2][3][4][5] The precursor films reacted with high-energy electrons and showed negative exposure characteristics. Some research groups fabricated functional metal-oxide micropatterns by an MOD method with EB irradiation using EB lithography (EBL) systems and succeeded in obtaining good physical properties.…”
mentioning
confidence: 99%
“…3) Tanabe et al fabricated YBa 2 Cu 3 O 7 micropatterns and succeeded in observing the superconductive transition. 4,5) This method can decrease drastically the number of fabrication steps for functional metal-oxide micropatterns, since only the EB-irradiation process is added to the conventional MOD method. Thus, this technique is very useful for forming micropatterns of various functional metal oxides using EBL systems, because it is difficult to etch functional metal oxides by a dry etching process.…”
mentioning
confidence: 99%
See 2 more Smart Citations